Protest or propaganda : war in the Old Testament book of Kings and in contemporaneous ancient Near Eastern texts - Deijl, Aarnoud van der. (Studia Semitica Neerlandica, 2008)
In this study, the war stories from the Old Testament book of Kings are compared to ten extrabiblical texts. Narratological analysis is applied to deconstruct the ideology of the respective literary compositions. The Old Testament ideology of war seems to be neither typically Israelite, as Gerhardt von Rad put it, nor commonly Ancient Near Eastern, as Manfred Weippert thought it to be. This poses the question whether the reading experience of biblical war stories is so very different from, for instance, Assyrian royal inscriptions, both in terms of its literary value and its ideological bias. Narratological analysis turns out to be a strong tool for explaining the similarities and distinctive features of the respective texts.